Regional Cooperation Governance in Urban Economic Development: A Strategic Study in Pangkalpinang City - Mayasari, Dessy; Zubaidah, Ida (Journal of Public Representative and Society Provision, 2025)
The city government of Pangkalpinang faces various urban challenges such as disparities in public services, inflationary pressures, and low competitiveness in strategic sectors. To address these issues, the city has implemented inter-regional and cross-sectoral cooperation aimed at strengthening development governance. This study seeks to analyze the forms of regional cooperation in the economic sector and their contribution to sustainable development. A mixed-methods approach was employed, focusing on eight Key Performance Indicators (KPIs). The findings reveal that the cooperation encompasses infrastructure development, economic and tourism promotion, metrological services, distribution of staple goods, waste-to-energy management, and fishery quality assurance. The partner satisfaction indicator recorded the highest performance score of 99.82%, indicating an effective partnership relationship. However, other indicators such as active agreements, inter-regional innovation, integrated planning, and MSME development scored below 50%, reflecting persistent challenges in coordination and institutional capacity. This suggests that although regional cooperation has had a positive impact on service efficiency and the local economy, substantial challenges remain. Future efforts should focus on strengthening joint planning, fostering innovation, enhancing collaboration, and empowering the microeconomic sector to ensure that regional cooperation becomes more inclusive and sustainable, positioning Pangkalpinang as a regional growth center in the Bangka Belitung Islands.